2007
DOI: 10.1080/14734220701225904
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the human cerebellum in eyeblink conditioning

Abstract: Besides its known importance for motor coordination, the cerebellum plays a major role in associative learning. The form of cerebellum-dependent associative learning, which has been examined in greatest detail, is classical conditioning of eyeblink responses. The much advanced knowledge of anatomical correlates, as well as cellular and molecular mechanisms involved in eyeblink conditioning in animal models are of particular importance because there is general acceptance that findings in humans parallel the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 112 publications
13
108
0
Order By: Relevance
“…In particular, the information collected has led to a better understanding of the physiological mechanisms underlying the role of cerebellar centers in neural control of movement (Eccles et al, 1967;Thach et al, 1992;Welsh and LlinĂĄs, 1997;Lang et al, 2006;Gerwig et al, 2007;Cheron et al, 2008). At the same time, recent analytical procedures have enabled the determination of how deep brain stimulation suppresses synchronized firing activities to improve its therapeutic efficiency in certain motor disorders (LlinĂĄs et al, 1999;Titcombe et al, 2001) by using different timedelayed feedback strategies (Rusemblum and Pikovski, 2004) and phase-resetting techniques (Tass, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the information collected has led to a better understanding of the physiological mechanisms underlying the role of cerebellar centers in neural control of movement (Eccles et al, 1967;Thach et al, 1992;Welsh and LlinĂĄs, 1997;Lang et al, 2006;Gerwig et al, 2007;Cheron et al, 2008). At the same time, recent analytical procedures have enabled the determination of how deep brain stimulation suppresses synchronized firing activities to improve its therapeutic efficiency in certain motor disorders (LlinĂĄs et al, 1999;Titcombe et al, 2001) by using different timedelayed feedback strategies (Rusemblum and Pikovski, 2004) and phase-resetting techniques (Tass, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The memory trace of the conditioned response (CR) acquired during classical eyeblink conditioning (Gormezano, Schneiderman, Deaux , & Fuentes, 1962) is thought to reside in the cerebellum (in humans see , Cheng Disterhoft, Power, Ellis, & Desmond, 2008;Gerwig, Kolb, & Timmann, 2007;in animals, Christian & Thompson, 2005;McCormick, Lavond, Clark, Kettner, Rising, & Thompson, 1981; for a review see Thompson, 2005). The hippocampus is not required for learning when the most simple (delay) form of eyeblink conditioning is applied (Schmaltz & Theios, 1972), but becomes increasingly important if the relations between the conditioning stimuli are more complex, like in trace conditioning (Berger & Orr, 1983;Moyer, Deyo, Disterhoft, 1990;Solomon, Vander Schaaf, Thompson, & Weisz, 1986) or when an unusually long inter-stimulus interval is used in delay conditioning (Beylin, Gandhi, Wood, Talk, Matzel, & Shors, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…When we try to move our lid by selfpaced, we should produce rhythm by ourselves. Previous studies have reported that the M1, primary somatosensory cortex, SMA, premotor cortex, and cerebellar hemisphere are related to the self generation of rhythmic movements (Gerwig et al 2007;Thaut et al 2008). Moreover, Spencer et al (2007) suggested that subregions of the cerebellum are selectively engaged during tasks involving event timing.…”
Section: Difference Between Self-paced Movement and Triggered Movementmentioning
confidence: 99%
“…Spontaneous blinks seem to arise from a central "blink generator" that can be influenced by several factors, such as visual and cognitive task requirements, and emotion. Neurobiological studies have identified the cerebellum and its brainstem connections as essential components of the eyeblink conditioning circuit (Gerwig et al 2007). Other forebrain areas, including basal ganglia, neocortex, and septal nuclei, have been less extensively studied but may also play a role in eyeblink conditioning.…”
Section: Difference Between Lid Opening/closing and Blinkingmentioning
confidence: 99%